Phospholipid remodeling and cholesterol availability regulate intestinal stemness and tumorigenesis - Wang, Bo (Cell Stem Cell, 2018)
Adequate availability of cellular building blocks, including lipids, is a prerequisite for cellular proliferation, but excess dietary lipids are linked to increased cancer risk. Despite these connections, specific regulatory relationships between membrane composition, intestinal stem cell (ISC) proliferation and tumorigenesis are unclear. We reveal an unexpected link between membrane phospholipid remodeling and cholesterol biosynthesis and demonstrate that cholesterol itself acts as a mitogen for ISCs. Inhibition of the phospholipid-remodeling enzyme Lpcat3 increases membrane saturation and stimulates cholesterol biosynthesis, thereby driving ISC proliferation. Pharmacologic inhibition of cholesterol synthesis normalizes crypt hyperproliferation in Lpcat3-deficient organoids and mice. Conversely, increasing cellular cholesterol content stimulates crypt organoid growth, and providing excess dietary cholesterol or driving endogenous cholesterol synthesis through SREBP-2 expression promotes ISC proliferation in vivo. Finally, disruption of Lpcat3-dependent phospholipid and cholesterol homeostasis dramatically enhances tumor formation in Apc(min) mice. These findings identify a critical dietary-responsive phospholipid-cholesterol axis regulating ISC proliferation and tumorigenesis.